Ternary hybrid nanofluid with first and second order velocity slips: dual solutions with stability analysis - Wahid, Nur Syahirah; Mohd Nasir, Nor Ain Azeany; Md Arifin, Norihan; Pop, Ioan (Tech Science Press, 2025)
Modeling the boundary layer flow of ternary hybrid nanofluids is important for understanding and optimizing their thermal performance, particularly in applications where enhanced heat transfer and fluid dynamics are essential. This study numerically investigates the boundary layer flow of alumina-copper-silver/water nanofluid over a permeable stretching/shrinking sheet, incorporating both first and second-order velocity slip. The mathematical model is solved in MATLAB facilitated by the bvp4c function that employs the finite difference scheme and Lobatto IIIa formula. The solver successfully generates dual solutions for the model, and further analysis is conducted to assess their stability. The findings reported that only one of the solutions is stable. For the shrinking sheet case, increasing the first-order velocity slip delays boundary layer separation and enhances heat transfer, while, when the sheet is stretched, the second-order velocity slip accelerates separation and improves heat transfer. Boundary layer separation is most likely to occur when the sheet is shrinking; however, this can be controlled by adjusting the velocity slip with the inclusion of boundary layer suction.